Free Indirect Discourse in Non-fiction - Stokke, Andreas (Frontiers in Communication, 2021)
This paper considers some uses of Free Indirect Discourse within non-fiction. The paper show that these are characterized by Free Indirect Discourse not being used to attribute inner speech. This motivates the conclusion that these uses of Free Indirect Discourse are not assertoric. Instead, it is argued here that they are fictional uses that introduce localized fictional scenarios from which audiences are meant to learn factual information. The paper suggests that, as such, these uses of Free Indirect Discourse exhibit some of the ways in which the involvement of perspective in historical fiction has been shown to facilitate learning and retention of information. Free Indirect Discourse is compared to Direct Discourse, and it is argued that the two are truth-conditionally equivalent.